Bisphenol A, an environmental estrogen-like toxic chemical, induces cardiac fibrosis by activating the ERK1/2 pathway. (27th May 2016) - Hu, Yingying; Zhang, Li; Wu, Xianxian; Hou, Liangyu; Li, Zhange; Ju, Jin; Li, Qian; Qin, Wei; Li, Jiamin; Zhang, Qingwei; Zhou, Tong; Zhang, Longyin; et al.
Highlights: Exposure to a high dosage of bisphenol A (BPA) comparable to its urinary concentration decreased cardiac function. BPA induced cardiac fibrosis. BPA markedly facilitated proliferation and collagen production of cardiac fibroblasts by activating ERK1/2. Antiestrogen or ERK inhibitor prevented BPA-induced proliferation and collagen production of cardiac fibroblasts, indicating that BPA acts by activating estrogen receptor and the ERK1/2-dependent pathways. Abstract: Bisphenol A (BPA) is a widely studied typical endocrine-disrupting chemical. The present study aimed to verify whether BPA could induce proliferation of cardiac fibroblasts and collagen production leading to cardiac interstitial fibrosis. After exposure to BPA for 30 consecutive days, decreased cardiac function was observed in rats using echocardiography, and the deposition of collagen was detected by Masson's trichrome staining and electron microscope. BPA remarkably stimulated proliferation and migration of cultured cardiac fibroblasts and collagen production in a concentration-dependent manner, as revealed by MTT, wound healing assay and collagen assay. Meanwhile, BPA treatment also enhanced phosphorylation of extracellular signal-regulated kinase 1/2 (ERK1/2). In contrast, pretreatment with estrogen receptor inhibitor ICI182780 or ERK inhibitor PD98059 prevented the enhanced phosphorylation of ERK1/2, and subsequently inhibited the up-regulation of transforming growth factor-β1 (TGF-β1) expression induced by BPA. As a consequence, these inhibitors also decreased proliferation and collagen production, as well as the fibrosis-related genes expression. Taken together, our results indicated that BPA may act as a promoting factor in proliferative process and collagen production of cardiac fibroblasts via activating ERK1/2.